The influence of board characteristics on sustainability reporting in selected Malaysian sensitive and non-sensitive industries - Ghuslan Mohamad Iruwan, Mohd Saleh Norman (Universiti Pendidikan Sultan Idris, 2017)
The influence of board characteristics on sustainability reporting in selected Malaysian sensitive and non-sensitive industries by Ghuslan Mohamad Iruwan, Mohd Saleh Norman,